Effectiveness of sodium bicarbonate and zinc chloride mouthwashes in the treatment of oral mucositis and quality of life in patients with cancer under chemotherapy. Issue 3 (16th February 2022) - Mohammadi, Fateme; Oshvandi, Khodayar; Kamallan, Seyed Ramesh; Khazaei, Salman; Ranjbar, Hossein; Ahmadi‐Motamayel, Fatemeh; Gillespie, Mark; Jenabi, Ensiyeh; Vafaei, Seyed Yaser
Abstract: Aim: The purpose of the study is to evaluate the effectiveness of sodium bicarbonate and zinc chloride mouthwashes on oral mucositis and quality of life in patients undergoing chemotherapy. Design: The present study was a randomized controlled trial study. Methods: One hundred forty‐four patients with a cancer diagnosis were randomly assigned into three groups: sodium bicarbonate mouthwash ( n  = 48), zinc chloride mouthwash ( n  = 48) and placebo group ( n  = 48). The severity of mucositis and quality of life were examined blindly at the baseline and 3‐week follow‐up. Results: The grade of oral mucositis decreased at the end of the third weeks in the sodium bicarbonate and zinc chloride groups rather than the placebo group ( p  < .001). The severity of oral mucositis in the sodium bicarbonate and zinc chloride groups decreased from end of the first week until third week ( p  < .001). In addition, there was significant difference in the severity of oral mucositis among the groups at the end of the second ( p  = .014) and the third weeks ( p  < .001). Also, there was a statistically significant difference in quality of life scores between the sodium bicarbonate and zinc chloride mouthwash with the placebo group ( p  < .001). Conclusion: Zinc chloride and sodium bicarbonate mouthwashes were effective in treating and reducing the severity of oral mucositis, and subsequently improving quality of life in patients with cancer under chemotherapy. Therefore, we can recommend zinc chloride and sodium bicarbonate at the beginning of chemotherapy to improve oral health and promoting quality of life in these patients.